Faktor Determinan Mahasiswa Tingkat Pertama Dalam Pengambilan Keputusan Memilih Program Studi Akuntansi S1 Universitas Negeri Padang - Charoline Cheisviyanny; Ravi Pratama (Universitas Negeri Padang, 2020)
This study aims to analyze the factors that determine first year accounting students in choosing an undergraduate accounting study program of Universitas Negeri Padang. These factors are interests, self-potential, parental support, job opportunities, costs, university image, collective decisions, school recommendation. The population in this study was the first year accounting students of Universitas Negeri Padang. The sample is determined based on the non-probability sampling method. The data used in this study are primary data. This study used a questionnaire to collect data. The analytical method is multiple linear regression analysis. The results showed interest, self-potential, and job opportunities have significant influences on decision making in selecting accounting study program of Universitas Negeri Padang. While parental support, fees, university assessments, collective decisions and school recommendation have no effect. Further researches are expected to explore other universities because each university has different charactetistics of students and a unique culture.